Acute effects of Spinning® session on body composition in healthy adults - Beyza Gurun; Cagdas Ozgur Cengizel; Elif Cengizel (ROL Spor Bilimleri Dergisi)
The purpose of this study was to determine the acute effects of Spinning® session on body composition in healthy adults. 32 healthy adults (9 men, 23 women) voluntarily participated in the study. The body composition of the participants was determined before and after Spinning® session by bioelectrical impedance analysis (BIA). A significant decrease in body weight, body fat, visceral fat level and metabolic age and significant increase in total body water, muscle mass, basal metabolic rate, physical activity level was determined in women after Spinning® session. A significant decrease in body weight, body fat, visceral fat level and significant increase in total body water, muscle mass, basal metabolic rate was found in men after Spinning® session. Although the decrease in metabolic age and the increase in physical activity level after Spinning® session in men, this difference was not significant. Spinning® exercise has a significant acute effect on body composition in healthy adults. In conclusion, Spinning® can be recommended as an alternative physical activity for sedentary individuals to have long-term beneficial effects, both because of the effects on body composition even with a single session and because it is a fun physical activity for healthy adults.